Low Level Continuous Heat Wraps can Increase the Efficiency of Transcutaneous Electrical Nerve Stimulation for Pain Management - Petrofsky, Jerrold; Laymon, Michael; Lee, Haneul (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2020)
Both transcutaneous electrical nerve stimulation and superficial heat have been used for pain management. While heat has been shown to have a beneficial effect on pain, transcutaneous electrical nerve stimulation remains controversial. The purpose of the present study was to see if heat, when added to transcutaneous electrical nerve stimulation, would provide more consistent relief. A total of 180 subjects participated in this study and were randomly divided into 12 groups. Low level continuous heat was applied while electrical stimulation was applied at 2 intensities, 2 frequencies and with 2 waveforms for 4 h. Outcome measures were subjective pain scale, range of motion of the back and skin blood flow of the back. The control groups had no significant difference in pain, range of motion or skin blood flow comparing the data at the beginning and 4 h after (p> 0.05). There was a small reduction in pain with transcutaneous electrical nerve stimulation alone while all other groups had a significant improvement in range of motion free of pain, reduction in pain, and increase in skin blood flow from the beginning to the end of the 4-hour period. Since transcutaneous electrical nerve stimulation with low level continuous heat showed better outcomes then transcutaneous electrical nerve stimulation alone or low level continuous heat alone, combining the 2 interventions seems to offer better outcomes for pain management for health care professionals.
Keywords: electrical stimulation; back pain; low level continuous heat; blood flow